2015
DOI: 10.1039/c4nr07648f
|View full text |Cite
|
Sign up to set email alerts
|

Structure dependent active sites of NixSy as electrocatalysts for hydrogen evolution reaction

Abstract: Structure effects of NiS and Ni3S2 nanoparticles were investigated for their electrocatalytic activity in the hydrogen evolution reaction in both acid and alkaline media. Owing to the different atomic configurations and crystalline structures, there is a hydrogen adsorption energy difference, which induces a difference in the activity. From density functional theory calculations and experimental observations, the importance of designing an electrocatalyst with an appropriate atomic configuration is evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…48 In our case, the Tafel slopes of all NiS x -m samples (101-148 mV/dec) implied that the rate determining step was the Volmer step, in which the proton adsorption played a key role. 23 In the case of NiS x -3 sample, the Tafel slope was the lowest, indicating that the proton adsorption was much easier than other NiS x samples. Therefore, it was inferred that the superior HER activity of NiS x -3 sample could originate from the much easier proton adsorption.…”
Section: Electrocatalytic Properties For Hydrogen Generationmentioning
confidence: 95%
See 1 more Smart Citation
“…48 In our case, the Tafel slopes of all NiS x -m samples (101-148 mV/dec) implied that the rate determining step was the Volmer step, in which the proton adsorption played a key role. 23 In the case of NiS x -3 sample, the Tafel slope was the lowest, indicating that the proton adsorption was much easier than other NiS x samples. Therefore, it was inferred that the superior HER activity of NiS x -3 sample could originate from the much easier proton adsorption.…”
Section: Electrocatalytic Properties For Hydrogen Generationmentioning
confidence: 95%
“…35 Sung and coworkers found that NiS and Ni 3 S 2 showed an apparent difference in electrocatalytic activity owing to their varied atomic configurations and crystalline structures. 23 Recently, Fu et al…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17][18][19][20] Among them, transition metal suldes such as molybdic sulde, [21][22][23] nickel sulde, [24][25][26] iron sulde 27 and cobalt sulde 28,29 have attracted considerable interest due to their earth abundance and high electrocatalytic activity. However, the poor conductivities of the transition metal suldes have limited their overall electrocatalytic performance, so they are always considered for loading on conductive substrates to improve the materials' electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…4,11,13 For instance, Chung et al experimentally found the superior HER performance of NiS over that of Ni 3 S 2 in alkaline media. 13 Jiang et al successfully synthesized Ni x S y with various phases including NiS, NiS 2 and Ni 3 S 2 by adjusting the amounts of S source, confirming the highest HER activity of Ni 3 S 2 in alkaline media. 11 However, these synthesis procedures are either complicated or energyguzzling.…”
mentioning
confidence: 99%
“…All potentials were calibrated to reversible hydrogen electrode (RHE) according to previous report. 13 All electrochemical data were presented with iR compensation. Figure 1 shows the morphologies of pristine Ni x S y and Ni x S y /rGO composites.…”
mentioning
confidence: 99%